Studying technological parameters of two-layer flatbread in bakeries of different used technologies - أمين موسى; شهيد مصطفى; حيدر خضور (Latakia University Journal -Biological Sciences Series, 2022)
Technological parameters of the two-layer flatbread were studied at different bakeries, the technologies used, and the production of the ration bread, and it was found that there are differences in the outputs of the manufacturing process related to the applied parameters, as most of the workers do not have this professional-skill or craftsmen. Seven indexes were selected: Index of water loss by baking process or evaporation index (index of inability to hold water), index of moisture retention after baking, index of upper part weight , index of bottom part weight , index of upper part moisture, index of bottom part moisture and index of relative standard deviation, where these indexes contributed to standardizing the basis for the correct comparison of results. To find out the nature of the relationships between the parameters with each other as well as their relationship with the indexes, the SPSS mathematical program was used to study the regression relationship and its best mathematical representation. It was found that the Power equation of the form: gave the best representation of the mathematical relationships for the most general of the correlations (8 cases) between an independent variable and a dependent variable. The Growth equation of the form: was able to excel in representation in only two cases.